2022
DOI: 10.3390/ijerph191811758
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health Literacy among University Health Science Students of Different Nationalities

Abstract: An adequate level of health literacy is essential for clear communication between patients and health care workers. The internationalization of universities is increasing in the field of health care. The aims of our research were to measure (1) the level of health literacy and its correlation among university students and (2) the relationship between the different instruments measuring health literacy. A cross-sectional study was conducted in the 2020/2021 academic year. The questionnaire included questions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Although these factors might have had some impact, only a weak relationship could be established. Specialization can be an in uencing factor (21), but in our study, no difference was shown between the healthy life scores of health-related students and students from other sectors.…”
Section: Discussioncontrasting
confidence: 81%
“…Although these factors might have had some impact, only a weak relationship could be established. Specialization can be an in uencing factor (21), but in our study, no difference was shown between the healthy life scores of health-related students and students from other sectors.…”
Section: Discussioncontrasting
confidence: 81%
“…Additionally, the study conducted by Bánfai-Csonka et al found that nationality was an influencing factor in HL among university health science students. The study reported a significant correlation between nationality and HL levels [38].…”
Section: Factors That Affect Health Literacy Levels In the Young Popu...mentioning
confidence: 74%